From India to China: Willow Branches and the Gender Transformation of Avalokiteśvara’s Iconography in China - Huang, Lele (Asia Social Issues, 2024)
Avalokiteśvara (Deity who looks down), known as Kuan-yin in China, becomes the most important deity and is popularized throughout Mahāyāna and Vajrayāna Buddhism. Avalokiteśvara, a Bodhisattva believed to have made a great vow to assist sentient beings in times of difficulty and to postpone his own Buddhahood until he has assisted every sentient being in achieving nirvana, experienced a long process of change. One of the striking changes in the image of Avalokiteśvara in China is the shifting of the gender of Avalokiteśvara. Kuan-yin became the most popular Bodhisattva during the Sui-Tang period (581-907 A.D.), and there were varied manifestations of the Kuan-yin image, one of the most popular being Willow Kuan-yin (Kuan-yin holding willow branches). Willow branches, associated with feminine qualities in Chinese culture, substituted the lotus in the iconography of Kuan-yin in China. This paper argues that the substitution of lotus for willow branches signifies the localization of Avalokiteśvara in China and, to an extent, pushed the gender transformation of this deity in the Chinese context.